Production process of copper foil and copper foil

By adding specific additives to the copper foil production process and performing surface treatment, the problem of the copper foil resistance to peel strength decreased after high-temperature treatment is solved, and higher peel strength and better weld resistance are achieved.

CN119685887APending Publication Date: 2025-03-25SHENZHEN HUIKE NEW MATERIALS CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411745735.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the production process of copper foil, the peel strength of copper foil is severely reduced after high temperature treatment, resulting in problems such as unqualified peel strength and explosive plates.

Method used

By adding additive C and additive D to the copper foil production process, performing surface roughening process and target temperature treatment, the anti-peel strength attenuation rate of the copper foil after high temperature treatment is reduced.

Benefits of technology

It effectively reduces the attenuation rate of the peel strength of the copper foil after high temperature treatment, ensures that the peel strength of the copper foil meets production needs, avoids explosive plates and improves the wet resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685887A_ABST
    Figure CN119685887A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of copper foils, and particularly relates to a production process of a copper foil and the copper foils, and the production process of the copper foils comprises the following steps: reacting a copper raw material with sulfuric acid to generate a copper sulfate solution; the copper sulfate solution is electrolyzed, and crude foil is obtained; the raw foil is subjected to surface treatment, the surface treatment comprises a roughening process, in the roughening process, a roughening solution comprises an additive C and an additive D, the additive C comprises one or a mixed solution of two or more of sodium tungstate, sodium molybdate, ammonium molybdate, tin sulfate and titanium sulfate, and the concentration of the additive C is 10-60 ppm; the additive D comprises high-molecular organic matters such as hydroxyethyl cellulose and ethylene glycol, and the concentration of the additive D is 30-50 ppm; and carrying out target temperature treatment on the crude foil subjected to the surface treatment to obtain the copper foil. Through the copper foil production process in the scheme, the peeling strength attenuation rate of the copper foil after high-temperature treatment can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of copper foil, and specifically relates to a production process of copper foil and copper foil. Background Art

[0002] Copper foil is a carrier of electronic and signal conduction in circuit boards. It is an important raw material in the manufacture of printed circuit boards (PCBs). It is one of the three key components of copper clad laminate (CCL) products and is known as the "neural network" for signal and power transmission and communication of electronic products. With the continuous development of electronic technology, the demand for high-frequency and high-speed products is increasing, and the requirements for low signal loss lines are constantly increasing, which has led to higher requirements for the physical properties (performance) of copper foil on the surface of the board.

[0003] However, in the production process of copper foil, after the copper foil is subjected to high-temperature treatment, the peeling strength will be seriously reduced, resulting in unqualified peeling strength and causing problems such as board explosion. Summary of the invention

[0004] The purpose of the present application is to provide a copper foil production process and copper foil, which can reduce the problem of decreased peeling strength of the copper foil after high-temperature treatment of the copper foil.

[0005] The first aspect of the present application provides a production process of copper foil, comprising the following steps:

[0006] reacting the copper raw material with sulfuric acid to form a copper sulfate solution;

[0007] electrolyzing the copper sulfate solution to obtain raw foil;

[0008] The raw foil is subjected to surface treatment, wherein the surface treatment includes a roughening process, wherein: the roughening solution includes an additive C and an additive D, wherein the additive C includes one or a mixed solution of two or more of sodium tungstate, sodium molybdate, ammonium molybdate, tin sulfate, and titanium sulfate, and the concentration of the additive C is 10-60 ppm; the additive D includes high molecular weight organic matter such as hydroxyethyl cellulose and ethylene glycol, and the concentration of the additive D is 30-50 ppm;

[0009] The raw foil after the surface treatment is subjected to a target temperature treatment to obtain a copper foil.

[0010] In an exemplary embodiment of the present application, in the roughening solution: the copper concentration is 11-18 g / L, and the sulfuric acid concentration is 100-150 g / L;

[0011] In the roughening process: the current density at the roughening inlet side is 33-40A / dm 2 The current density at the roughening outlet side is 0.6-0.8 times the current density at the roughening inlet side.

[0012] In an exemplary embodiment of the present application, after reacting the copper raw material with sulfuric acid to generate a copper sulfate solution, the following steps are further included:

[0013] The obtained copper sulfate solution is filtered for the first time, and a first additive is added to the copper sulfate solution after the first filtration, wherein the first additive includes additive A and additive B, wherein additive A includes macromolecular gelatin, and additive B includes small molecule collagen peptide, and the concentration ratio of additive A to additive B is 1:1, and the concentration of the first additive is 0.67-1.06 ppm;

[0014] The copper sulfate solution to which the first additive has been added is filtered a second time.

[0015] In an exemplary embodiment of the present application, the step of adding the first additive to the copper sulfate solution after the first filtration also includes:

[0016] Activated carbon is added, and the added concentration of the activated carbon is 1-1.3 times the concentration of the first additive.

[0017] In an exemplary embodiment of the present application, the molecular weight of the additive A is 100,000-250,000 Da, and the molecular weight of the additive B is 1200-1800 Da.

[0018] In an exemplary embodiment of the present application, the process steps of filtering the pure copper sulfate solution to which the first additive is added for a second time include:

[0019] The pure copper sulfate solution to which the first additive is added is filtered for a second time using an ultrafiltration membrane with a precision of 0.45 μm.

[0020] In an exemplary embodiment of the present application, the surface treatment further comprises pickling;

[0021] Wherein, in the pickling process: the concentration of sulfuric acid is 80-150 g / L, the mass concentration of hydrogen peroxide is 5%-12%, and the ratio of hydrogen peroxide to sulfuric acid is 1:1-1.25.

[0022] In an exemplary embodiment of the present application, the surface treatment further comprises curing;

[0023] In the curing process: the copper ion concentration is 60-85 g / L, and the sulfuric acid concentration is 70-90 g / L;

[0024] Among them, the curing inlet current density is 38-45A / dm 2 , the curing outlet current density is 0.8-0.95 times the curing inlet current density.

[0025] In an exemplary embodiment of the present application, the surface treatment further includes at least one of ashing, passivation and organization;

[0026] The ashing process includes: electroplating a zinc-nickel alloy layer with a current density of 1.5-2.5A / dm 2 ; and / or

[0027] The passivation process includes: the passivation current density is 3.0-6.0A / dm 2 ; and / or

[0028] The organic process includes: coating the rough surface of the raw foil with silane; the silane is a mixed solution prepared by mixing γ-glycidyloxypropyltrimethoxysilane, N-2aminoethyl-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane and water, and the concentration of the silane is 5‰-10‰.

[0029] A second aspect of the present application provides a copper foil prepared by any of the preparation processes described above.

[0030] The present application includes a production process of copper foil and the copper foil has at least the following beneficial effects:

[0031] In the present application, additives C and additive D are added to the roughening process of the raw foil surface treatment. The peel strength decay rate of the copper foil added with additives C and additive D after high-temperature treatment is reduced. That is, by adding additives C and additive D to the roughening process, the peel strength decay rate of the copper foil under high-temperature treatment can be reduced, thereby ensuring the peel strength of the copper foil.

[0032] Other features and advantages of the present application will become apparent from the following detailed description, or may be learned in part by the practice of the present application.

[0033] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present application, and together with the specification are used to explain the principles of the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0035] Figure 1 A schematic diagram of the copper foil production process provided in Example 1 or Example 2 of the present application is shown.

[0036] Figure 2It shows the steps provided in Example 1 or Example 2 of the present application before electrolyzing the copper sulfate solution. DETAILED DESCRIPTION

[0037] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the examples set forth herein; rather, these embodiments are provided so that this application will be more comprehensive and complete and fully convey the concept of the example embodiments to those skilled in the art.

[0038] In this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0039] In this application, unless otherwise clearly specified and limited, the terms "assembly", "connection" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0040] In addition, described feature, structure or characteristic can be combined in one or more embodiments in any suitable manner. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present application. However, those skilled in the art will appreciate that the technical scheme of the present application can be put into practice without one or more of the specific details, or other methods, components, devices, steps, etc. can be adopted. In other cases, known methods, devices, realizations or operations are not shown or described in detail to avoid blurring the various aspects of the application.

[0041] In the prior art, after the copper foil is baked at 200°C for 8 hours, its peel strength decreases from 2.2-2.4kg*f / cm before drying to 0.5-0.8kg*f / cm after baking, and its attenuation rate after high-temperature baking is ≥50%, which can easily lead to unqualified peel resistance after high-temperature treatment, causing board explosion, poor resistance to immersion soldering and other problems.

[0042] Embodiment 1

[0043] In order to solve the above problems, the present application provides a copper foil production process. Figure 1 As shown, it includes the following steps:

[0044] Step S100, reacting a copper raw material with sulfuric acid to generate a copper sulfate solution;

[0045] Step S200, electrolyzing the copper sulfate solution to obtain raw foil;

[0046] Step S300, performing surface treatment on the raw foil, the surface treatment including a roughening process, adding additives C and additives D in the roughening process;

[0047] Step S400, subjecting the raw foil after the surface treatment to a target temperature treatment to obtain an electrolytic copper foil.

[0048] The copper foil obtained by the above process has less attenuation of peel strength after high temperature treatment, ensuring that the peel strength meets the production requirements, avoiding board explosion, and improving resistance to immersion soldering.

[0049] The step S100 specifically includes: adding copper oxide wire with a copper purity of ≥99.9% into a copper dissolving tank, and adding sulfuric acid into the copper dissolving tank, stirring, heating, and reacting to generate a copper sulfate solution. It is worth mentioning that the copper dissolving temperature is 55-62°C, and the copper dissolving temperature can be: 55°C, 58°C, 60°C, 62°C, etc.

[0050] It can be understood that this step S100 is mainly to dissolve the solidified copper wire into a copper sulfate solution, the purpose of which is to make the copper ions in a free state to facilitate the formation of a subsequent electrolyte.

[0051] Before electrolysis of copper sulfate solution, see Figure 2 As shown, the following steps are also included:

[0052] Step S110, filtering the obtained copper sulfate solution for the first time, and adding a first additive to the copper sulfate solution after the first filtration;

[0053] Step S120, filtering the copper sulfate solution to which the first additive is added for a second time.

[0054] Step S110 mainly includes using a diatomaceous earth medium with a filtering accuracy of 1 μm. This step is because the raw copper wire contains impurities, and the impurities are filtered using the diatomaceous earth medium to improve the purity of the copper sulfate solution.

[0055] And in step S110, the first additive added to the pure copper sulfate solution includes additive A and additive B, wherein additive A is macromolecular gelatin with a molecular weight of 100,000-250,000 Da, and additive B is a small molecule collagen peptide with a molecular weight of 1200-1800 Da. Among them, the ratio of additive A to additive B is 1:1, and the addition concentration of the first additive formed by additive A and additive B is 0.67-1.06 ppm, for example, it can be: 0.67 ppm, 0.88 ppm, 1.00 ppm, 1.06 ppm. By adding the first additive, the crystal plane arrangement of the subsequent copper foil can be controlled, that is, the proportion of the crystal plane index <2 2 0> of the copper foil can be controlled.

[0056] Wherein, step S110 also includes adding activated carbon, and the added concentration of the activated carbon is 1-1.3 times the concentration of the first additive, for example, 0.7, 0.8, 0.924. The activated carbon can absorb organic impurities in the pure copper sulfate solution to ensure the purity of the copper sulfate solution.

[0057] The second filtration in step S120 uses an ultrafiltration membrane with a precision of 0.45 μm to filter the copper sulfate solution again to further improve the purity of the copper sulfate solution.

[0058] After the second filtration, the copper sulfate solution has fewer internal impurities and higher purity, and is then discharged into the electrolytic cell to prepare for electrolysis.

[0059] Step S200 includes: sending the electrolyte formed after the second filtration to the electrolytic cell, at a raw foil temperature of 50-55°C, for example: 50°C, 52°C, 53.5°C, 55°C; a current density of 75-90A / dm 2 , for example, 75A / dm 2 、80A / dm 2 、83A / dm 2 、87A / dm 2 、90A / dm 2 Electrodeposition is carried out on a cathode roller to obtain a raw foil.

[0060] It is worth mentioning that the surface roughness of raw foils of different ounces is different. For example, the roughness Rz of the raw foil of 1 ounce is controlled at 6.2-6.9μm, and the proportion of the crystal plane index <2 2 0> is 80%-87%; the roughness Rz of the raw foil of 2 ounce is controlled at 9.0-9.8μm, and the proportion of the crystal plane index <2 2 0> is 80%-87%.

[0061] In step S300, the surface treatment of the raw foil includes six stages: pickling, roughening, curing, ashing, passivation, and organization.

[0062] In the pickling stage: the pickling solution in the pickling tank is a mixed solution of sulfuric acid and hydrogen peroxide, the concentration of sulfuric acid is 80-150g / L, for example: 80g / L, 90g / L, 120g / L, 130g / L, 150g / L; the mass concentration of hydrogen peroxide is 5%-12%, for example, 5%, 7%, 9%, 12%. It is worth mentioning that the pickling solution is made by blending hydrogen peroxide and sulfuric acid in a certain proportion, and the ratio of hydrogen peroxide to sulfuric acid can be 1:1-1.25, for example: 1:1, 1:1.05, 1:1.2, 1:1.25. Pickling can remove copper oxide on the surface of raw foil and expose more active points.

[0063] In the roughening stage: the roughening solution in the roughening tank contains a copper concentration of 11-18 g / L, a sulfuric acid concentration of 100-150 g / L, and additives C and D. Among them, the copper concentration can be 11 g / L, 12.5 g / L, 14 g / L, 16 g / L, etc. The sulfuric acid concentration can be 100 g / L, 130 g / L, 150 g / L. The additive C includes a mixed solution of one or two or more of sodium tungstate, sodium molybdate, ammonium molybdate, tin sulfate, and titanium sulfate. The concentration of the additive C is 10-60 ppm, for example: 10 ppm, 20 ppm, 30 ppm, 50 ppm, 60 ppm, and this additive C can mainly inhibit the longitudinal growth of tumor cuprous oxide. Additive D includes high molecular organic matter such as hydroxyethyl cellulose and ethylene glycol, and the concentration of the additive D is 30-50 ppm, for example: 30 ppm, 40 ppm, 50 ppm, and the additive D mainly functions to control the lateral growth of copper ions.

[0064] In addition, during the roughening stage, the roughening inlet and outlet sides have a certain current density, and the current density of the roughening inlet side is 33-40A / dm 2 , for example: 33A / dm 2 、36A / dm 2 、39A / dm 2 、40A / dm 2 ; The current density at the roughening outlet is 0.6-0.8 times the current density at the roughening inlet, for example, 19A / dm 2 , 20A / dm 2 、30A / dm 2 、32A / dm 2 .

[0065] During the curing stage, the curing liquid in the curing tank contains 60-85g / L copper ions and 70-90g / L sulfuric acid. The curing liquid can be 60g / L copper ions and 70g / L sulfuric acid; it can also be 72.5g / L copper ions and 82g / L sulfuric acid; it can also be 85g / L copper ions and 90g / L sulfuric acid. The curing inlet current density is 38-45A / dm2 , for example: 38A / dm 2 、40A / dm 2 、43A / dm 2 、45A / dm 2 ; The curing current density at the outlet is 0.8-0.95 times the current density at the inlet, for example: 31A / dm 2 、35A / dm 2 、38A / dm 2 、42A / dm 2 .

[0066] In the ashing stage, a conventional electroplated zinc-nickel alloy layer is used with a current density of 1.5-2.5A / dm 2 , for example, 1.5A / dm 2 , 1.75A / dm 2 , 2A / dm 2 , 2.5A / dm 2 .

[0067] In the passivation stage, the passivation current density is 3.0-6.0A / dm 2 , for example, 3.0A / dm 2 , 3.3A / dm 2 , 4A / dm 2 , 5A / dm 2 、6A / dm 2 .

[0068] In the organic stage, the rough surface of the raw foil is coated with silane, and the silane is a mixed solution of γ-glycidyloxypropyltrimethoxysilane, N-2aminoethyl-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane and water. The concentration of the silane is 5‰-10‰, for example: 5‰, 6‰, 7‰, 8‰, 9‰, 10‰.

[0069] It is worth mentioning that when the raw foil generated after electrolysis is subjected to surface treatment, three solidification steps and three roughening steps are performed respectively. Roughening and solidification are performed in an interlaced manner, and the composition of the roughening liquid in each roughening stage is the same as that described in the above roughening process; the composition of the solidifying liquid in each solidification stage is the same as that described in the above solidification process.

[0070] In step S400, the raw foil after surface treatment needs to be subjected to target temperature treatment, and the target temperature may be 200°C or 220°C. The target temperature may be determined according to the baking temperature of the copper foil produced.

[0071] In the embodiment of the present application, the raw foil is surface treated by baking at 200°C for 8 hours. The copper foil formed after high-temperature baking in the present application has a small attenuation of peel strength and can still maintain a high peel strength, thereby manufacturing a copper foil that meets the peel strength requirements, avoiding the occurrence of board explosion, and improving the resistance to immersion soldering.

[0072] Example 1

[0073] Example 1 provides a production process for copper foil, which includes the following steps in order: copper dissolving, first filtration, adding a first additive, second filtration, foil production, surface treatment, and high temperature treatment.

[0074] Among them, in the copper dissolving process, the copper dissolving temperature is 58°C, and a copper sulfate solution is generated.

[0075] The generated copper sulfate solution is filtered for the first time to obtain a pure copper sulfate solution. The first filtration uses a diatomaceous earth medium with a filtration accuracy of 1 μm.

[0076] The first additive and activated carbon were added to the pure copper sulfate solution. The concentration of the first additive was 0.88 ppm, and the concentration of the activated carbon was 0.924 ppm.

[0077] The purified copper sulfate solution to which the first additive and activated carbon are added is filtered for the second time to generate an electrolyte. The second filtration uses an ultrafiltration membrane with a precision of 0.45 μm.

[0078] At a raw foil temperature of 53.5°C and a current density of 83A / dm 2 Under the conditions of , green foil is produced on the cathode roller.

[0079] Among them, the roughness Rz of the rough surface of 1 ounce raw foil is 6.3μm, and the proportion of the crystal plane index <2 2 0> is 84%. The roughness Rz of the rough surface of 2 ounce raw foil is 9.3μm, and the proportion of the crystal plane index <2 2 0> is 81%.

[0080] 1 oz and 2 oz raw foils are surface treated and the surface treatment includes:

[0081] Pickling: The concentration of sulfuric acid in the pickling solution is 120-125g / L, hydrogen peroxide: sulfuric acid = 1:1.05. The concentration of sulfuric acid can be 120g / L, 121g / L, 122g / L, 123g / L, 124g / L, 125g / L.

[0082] Roughening: The copper ion concentration in the roughening solution is 12.5 g / L, the sulfuric acid concentration is 130 g / L, the concentration of additive C is 20 ppm, of which the sodium tungstate concentration is 2.5 ppm, and the ammonium molybdate concentration is 17.5 ppm. The concentration of additive D is 40 ppm, of which the hydroxyethyl cellulose concentration is 40 ppm, that is, additive D is composed of hydroxyethyl cellulose. The current density on the roughening inlet side is 39 A / dm 2 , the current density on the roughening side is 30A / dm 2 .

[0083] Curing: The copper ion concentration in the curing liquid is 72.5g / L. The sulfuric acid concentration is 82g / L. The curing inlet current density is 43A / dm 2 The curing current density is 38A / dm 2 .

[0084] Ashing: Ashing current density is 1.75A / dm 2 .

[0085] Passivation: Passivation current density is 3.3A / dm 2 .

[0086] Organization: Silane is prepared by mixing γ-glycidyloxypropyltrimethoxysilane with water at a concentration of 6‰.

[0087] Before high temperature baking treatment, the peel strength of the 1 ounce green foil is 2.32 kg*f / cm, and the peel strength of the 2 ounce green foil is 3.12 kg*f / cm.

[0088] The surface treated raw foil was subjected to high temperature treatment. The peel strength of 1 ounce raw foil was reduced to 1.46 kg*f / cm after being baked at 200℃ for 8h-10h, and the peel strength of 2 ounce raw foil was reduced to 1.76 kg*f / cm after being baked at 200℃ for 8h-10h. The peel attenuation rates of 1 ounce and 2 ounce raw foil were 37.06% and 43.59% respectively.

[0089] By adding additives C and D to the roughening solution, the anti-peeling attenuation rate of the copper foil under high temperature treatment can be effectively reduced, ensuring that the copper foil meets the anti-peeling strength requirements.

[0090] Example 2

[0091] Example 2 provides a production process for copper foil, which includes the following steps in order: copper dissolving, first filtration, adding a first additive, second filtration, foil production, surface treatment, and high temperature treatment.

[0092] Among them, in the copper dissolving process, the copper dissolving temperature is 62°C, and a copper sulfate solution is generated.

[0093] The generated copper sulfate solution is filtered for the first time to obtain a pure copper sulfate solution. The first filtration uses a diatomaceous earth medium with a filtration accuracy of 1 μm.

[0094] A first additive and activated carbon were added to the pure copper sulfate solution. The concentration of the first additive was 0.88 ppm, and the concentration of the activated carbon was 0.924 ppm.

[0095] The purified copper sulfate solution to which the first additive and activated carbon are added is filtered for the second time to generate an electrolyte. The second filtration uses an ultrafiltration membrane with a precision of 0.45 μm.

[0096] At a raw foil temperature of 52.5°C and a current density of 78A / dm 2 Under the conditions of , green foil is produced on the cathode roller.

[0097] Among them, the roughness Rz of the rough surface of 1 ounce raw foil is 6.5μm, and the proportion of crystal plane index <2 2 0> is 79%. The roughness Rz of the rough surface of 2 ounce raw foil is 9.5μm, and the proportion of crystal plane index <2 2 0> is 77%.

[0098] Surface treatments are applied to 1oz and 2oz raw foils, including:

[0099] Pickling: The concentration of sulfuric acid in the pickling solution is 124g / L, hydrogen peroxide: sulfuric acid = 1:1.05.

[0100] Roughening: The copper ion concentration in the roughening solution is 11.5 g / L, the sulfuric acid concentration is 135 g / L, the concentration of additive C is 25 ppm, of which the sodium tungstate concentration is 3.6 ppm and the ammonium molybdate concentration is 21.4 ppm. The concentration of additive D is 35 ppm, of which the hydroxyethyl cellulose concentration is 40 ppm, that is, additive D is composed of hydroxyethyl cellulose. The current density on the roughening inlet side is 39 A / dm 2 , the current density on the roughening side is 30A / dm 2 .

[0101] Curing: The copper ion concentration in the curing liquid is 72.5g / L. The sulfuric acid concentration is 82g / L. The curing inlet current density is 43A / dm 2 The curing current density is 38A / dm 2 .

[0102] Ashing: Ashing current density is 1.75A / dm 2 .

[0103] Passivation: Passivation current density is 3.3A / dm 2 .

[0104] Organization: Silane is prepared by mixing γ-glycidyloxypropyltrimethoxysilane with water at a concentration of 6‰.

[0105] Before high temperature baking treatment, the peel strength of the 1 ounce green foil is 2.32 kg*f / cm, and the peel strength of the 2 ounce green foil is 3.12 kg*f / cm.

[0106] The surface treated raw foil was subjected to high temperature treatment. The peel strength of 1 ounce raw foil was reduced to 1.46 kg*f / cm after being baked at 200℃ for 8h-10h, and the peel strength of 2 ounce raw foil was reduced to 1.76 kg*f / cm after being baked at 200℃ for 8h-10h. The peel attenuation rates of 1 ounce and 2 ounce raw foil were 37.06% and 43.59% respectively.

[0107] By adding additives C and D to the roughening solution, the anti-peeling attenuation rate of the copper foil under high temperature treatment can be effectively reduced, ensuring that the copper foil meets the anti-peeling strength requirements.

[0108] Example 3

[0109] Example 3 provides a production process for copper foil, which includes the following steps in order: copper dissolving, first filtration, adding a first additive, second filtration, foil production, surface treatment, and high temperature treatment.

[0110] Among them, in the copper dissolving process, the copper dissolving temperature is 62°C, generating a copper sulfate solution.

[0111] The generated copper sulfate solution is filtered for the first time to obtain a pure copper sulfate solution. The first filtration uses a diatomaceous earth medium with a filtration accuracy of 1 μm.

[0112] The first additive and activated carbon were added to the pure copper sulfate solution. The concentration of the first additive was 1.03 ppm, and the concentration of the activated carbon was 1.133 ppm.

[0113] The purified copper sulfate solution to which the first additive and activated carbon are added is filtered for the second time to generate an electrolyte. The second filtration uses an ultrafiltration membrane with a precision of 0.45 μm.

[0114] At a raw foil temperature of 52.5°C and a current density of 80A / dm 2 Under the conditions of , green foil is produced on the cathode roller.

[0115] Among them, the roughness Rz of the rough surface of 1 ounce raw foil is 6.7μm, and the proportion of crystal plane index <2 2 0> is 87%. The roughness Rz of the rough surface of 2 ounce raw foil is 9.7μm, and the proportion of crystal plane index <2 2 0> is 83%.

[0116] Surface treatments are applied to 1oz and 2oz raw foils, including:

[0117] Pickling: The concentration of sulfuric acid in the pickling solution is 120-125g / L, hydrogen peroxide: sulfuric acid = 1:1.05. The concentration of sulfuric acid can be 120g / L, 121g / L, 122g / L, 123g / L, 124g / L, 125g / L.

[0118] Roughening: The copper ion concentration in the roughening solution is 13.5 g / L, the sulfuric acid concentration is 135 g / L, the concentration of additive C is 18 ppm, of which the sodium tungstate concentration is 1.5 ppm and the ammonium molybdate concentration is 16.5 ppm. The concentration of additive D is 45 ppm, of which the hydroxyethyl cellulose concentration is 25 ppm and the polyethylene glycol concentration is 20 ppm. The current density on the roughening inlet side is 38.2 A / dm 2 The current density on the roughening side is 23A / dm 2 .

[0119] Curing: The copper ion concentration in the curing liquid is 67.5g / L. The sulfuric acid concentration is 75g / L. The curing inlet current density is 47A / dm 2 The curing current density is 38A / dm 2 .

[0120] Ashing: Ashing current density is 1.85A / dm 2 .

[0121] Passivation: Passivation current density is 3.0A / dm 2 .

[0122] Organization: Silane is prepared by mixing N-2-aminoethyl-3-aminopropyltrimethoxysilane with water at a concentration of 6‰.

[0123] Before high temperature baking treatment, the peel strength of the 1 ounce green foil is 2.35 kg*f / cm, and the peel strength of the 2 ounce green foil is 3.28 kg*f / cm.

[0124] The surface treated raw foil was subjected to high temperature treatment. The peel strength of 1 ounce raw foil was reduced to 1.64 kg*f / cm after being baked at 200℃ for 8h-10h, and the peel strength of 2 ounce raw foil was reduced to 1.89 kg*f / cm after being baked at 200℃ for 8h-10h. The peel attenuation rates of 1 ounce and 2 ounce raw foil were 30.21% and 42.38% respectively.

[0125] By adding additives C and D to the roughening solution, the anti-peeling attenuation rate of the copper foil under high temperature treatment can be effectively reduced, ensuring that the copper foil meets the anti-peeling strength requirements.

[0126] Comparative Example

[0127] Table 1 below shows the decay rates of raw foils of different specifications without the addition of additive C and additive D in the roughening process:

[0128]

[0129] Table 1

[0130] In Table 1 above, additives C and D are not added to the roughening liquid of the roughening process. After the raw foil is baked at high temperature, the peel strength attenuation rate of raw foils of different specifications is reduced by more than 50%, resulting in unqualified peel strength of the copper foil, easy to cause board explosion and poor resistance to immersion soldering.

[0131] The present application adds additives C and D to the roughening liquid, which can effectively reduce the peel strength attenuation rate of the copper foil after high-temperature baking treatment, ensure that the peel strength of the copper foil is qualified, and will not cause problems such as board explosion, thereby improving the solder resistance of the copper foil and thus improving the quality of the copper foil.

[0132] Embodiment 2

[0133] Embodiment 2 of the present application provides a copper foil, which is prepared by using the preparation process in the above embodiment 1. The copper foil prepared by the above preparation process has a low peel strength attenuation rate, thereby ensuring qualified peel strength and improving the solder immersion resistance of the copper foil.

[0134] In the description of this specification, the description with reference to the terms "some embodiments", "exemplarily", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0135] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application. Therefore, any changes or modifications made in accordance with the claims and description of the present application should fall within the scope of the patent of this application.

Claims

1. A production process for copper foil, characterized in that: The steps include: reacting the copper raw material with sulfuric acid to form a copper sulfate solution; electrolyzing the copper sulfate solution to obtain raw foil; The raw foil is subjected to surface treatment, wherein the surface treatment includes a roughening process, wherein: the roughening solution includes an additive C and an additive D, wherein the additive C includes one or a mixed solution of two or more of sodium tungstate, sodium molybdate, ammonium molybdate, tin sulfate, and titanium sulfate, and the concentration of the additive C is 10-60 ppm; the additive D includes high molecular weight organic matter such as hydroxyethyl cellulose and ethylene glycol, and the concentration of the additive D is 30-50 ppm; The raw foil after the surface treatment is subjected to a target temperature treatment to obtain a copper foil.

2. The production process of copper foil according to claim 1, characterized in that: In the roughening solution: the copper concentration is 11-18 g / L, and the sulfuric acid concentration is 100-150 g / L; In the roughening process: the current density at the roughening inlet side is 33-40A / dm 2 , the current density at the roughening outlet side is 0.6-0.8 times the current density at the roughening inlet side.

3. The production process of copper foil according to claim 1, characterized in that: After the copper raw material is reacted with sulfuric acid to generate a copper sulfate solution, the following steps are also included: The obtained copper sulfate solution is filtered for the first time, and a first additive is added to the copper sulfate solution after the first filtration, wherein the first additive includes additive A and additive B, wherein additive A includes macromolecular gelatin, and additive B includes small molecule collagen peptide, and the concentration ratio of additive A to additive B is 1:1, and the concentration of the first additive is 0.67-1.06 ppm; The copper sulfate solution to which the first additive is added is filtered for the second time.

4. The production process of copper foil according to claim 3, characterized in that: The step of adding the first additive to the copper sulfate solution after the first filtration also includes: Activated carbon is added, and the added concentration of the activated carbon is 1-1.3 times the concentration of the first additive.

5. The production process of copper foil according to claim 3, characterized in that: The molecular weight of the additive A is 100,000-250,000 Da, and the molecular weight of the additive B is 1200-1800 Da.

6. The production process of copper foil according to claim 1, characterized in that: The process steps of filtering the purified copper sulfate solution to which the first additive is added for a second time include: The pure copper sulfate solution to which the first additive is added is filtered for a second time using an ultrafiltration membrane with a precision of 0.45 μm.

7. The production process of copper foil according to claim 1, characterized in that: The surface treatment also includes pickling; Wherein, in the pickling process: the concentration of sulfuric acid is 80-150 g / L, the mass concentration of hydrogen peroxide is 5%-12%, and the ratio of hydrogen peroxide to sulfuric acid is 1:1-1.

25.

8. The production process of copper foil according to claim 1, characterized in that: The surface treatment also includes curing; In the curing process: the copper ion concentration is 60-85 g / L, and the sulfuric acid concentration is 70-90 g / L; Among them, the curing inlet current density is 38-45A / dm 2 , the curing outlet current density is 0.8-0.95 times the curing inlet current density.

9. The production process of copper foil according to claim 1, characterized in that: The surface treatment also includes at least one of ashing, passivation and organization; The ashing process includes: electroplating a zinc-nickel alloy layer with a current density of 1.5-2.5A / dm 2 ; and / or The passivation process includes: the passivation current density is 3.0-6.0A / dm 2 ; and / or The organic process includes: coating the rough surface of the raw foil with silane; the silane is a mixed solution prepared by mixing γ-glycidyloxypropyltrimethoxysilane, N-2aminoethyl-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane and water, and the concentration of the silane is 5‰-10‰.

10. A copper foil, characterized in that: The invention is prepared by the preparation process according to any one of claims 1 to 9.

Citation Information

Cited By

  • High-strength VLP copper foil for ultra-high-precision PCB and preparation method of high-strength VLP copper foil

    CN120485893A

  • Electrolytic copper foil and roughening treatment method thereof

    CN122105552A